Case report: Case series featuring anastomotic colonic adenocarcinoma following jejunoileal bypass requiring oncologic resection and jejunoileal bypass reversal - Miles, Bryan; Visioni, Anthony; Daigle, Christopher; Marley, Robert; Brandstetter, Stephen (Frontiers in Surgery, 2023)
Like all surgical fields, bariatric surgery has evolved immensely, so much so that previous procedures are now obsolete. For instance, the jejunoileal bypass (JIB) has fallen by the wayside after severe metabolic consequences resulted in prolonged morbidity and even mortality. Despite this, several patients persevered long enough to develop other pathology, such as cancer. This progression has been validated in animal models, but not human subjects. Nonetheless, contemporary surgeons may encounter situations where they must resect and reestablish intestinal continuity in patients with this antiquated anatomy. When faced with this scenario, the question of whether or not the previously bypassed small bowel can be safely reunited plagues the surgeon. Unfortunately, the literature does not effectively answer this question, even anecdotally through case reports or series. Therefore, we share our experience with three patients who developed colon cancer following jejunoileal bypass and subsequently underwent oncologic resection with simultaneous reversal of their jejunoileal bypasses.